2018
DOI: 10.1159/000490334
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Renal Afferent Arteriolar Reactive Oxygen Species and Contractility to Endothelin-1 Are Associated with Canonical Wnt Signaling in Diabetic Mice

Abstract: Background/Aims: Canonical Wnt signaling is involved in oxidative stress, vasculopathy and diabetes mellitus but its role in diabetic renal microvascular dysfunction is unclear. We tested the hypothesis that enhanced canonical Wnt signaling in renal afferent arterioles from diabetic mice increases reactive oxygen species (ROS) and contractions to endothelin-1 (ET-1). Methods: Streptozotocin-induced diabetes or control C57Bl/6 mice received vehicle or sulindac (40 mg·kg-1·day-1) to block W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 49 publications
(58 reference statements)
0
5
0
Order By: Relevance
“…An increase in ROS can influence cell signaling proteins and their functional consequences. In a previous study, signaling pathways were shown to be targeted by ROS, including NF-κB, MAPKs, PI3K/AKT, Wnt/β-catenin, and ion channel signaling [13,15,16]. To determine the role of PI3K/AKT signaling in cell proliferation and apoptosis of HLECs, we used the PI3K inhibitor, LY294002, to determine the effects on cell growth and apoptosis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…An increase in ROS can influence cell signaling proteins and their functional consequences. In a previous study, signaling pathways were shown to be targeted by ROS, including NF-κB, MAPKs, PI3K/AKT, Wnt/β-catenin, and ion channel signaling [13,15,16]. To determine the role of PI3K/AKT signaling in cell proliferation and apoptosis of HLECs, we used the PI3K inhibitor, LY294002, to determine the effects on cell growth and apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Changes in the ethidium to dihydroethidium (E: DHE) fluorescence ratio and 6-carboxy-2′,7′-dichlorodihydrofluorescein diacetate (C-H 2 DCFDA) (Sigma, St. Louis, MO, USA) were used for detection of superoxide (O 2 − ) and hydrogen peroxide (H 2 O 2 ), respectively, which were analyzed using standard assay kits, according to the manufacturer’s instructions [13,20]. The O 2 − and H 2 O 2 levels were presented as units or μmol per milligram of protein.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In afferent arterioles, NOX2-dependent superoxide formation contributes to the development of vasoconstriction elicited by angiotensin II [66]. Also, the endothelin-1-induced vasoconstriction in the renal microcirculation depends on superoxide, whose source is not yet determined [67,68]. Furthermore, sphingosine 1-phosphate-induced vasoconstrictions of afferent arterioles could be inhibited by the NOX inhibitor apocynin, suggesting that NOX-dependent superoxide formation contributes to this vasoconstriction [69].…”
Section: Ros and Renal Vascular Tone Regulationmentioning
confidence: 99%
“…and exogenous (vitamin C, vitamin E, carotenoids, etc.) antioxidants [ 10 , 11 , 12 ]. Oxidative damage also increases the release of cytochrome c from the mitochondria into the cytosol, which acts as the major initiator of the apoptotic signaling cascade [ 7 , 13 ].…”
Section: Introductionmentioning
confidence: 99%